2015
DOI: 10.4236/jwarp.2015.714094
|View full text |Cite
|
Sign up to set email alerts
|

Greywater Treatment by High Rate Algal Pond under Sahelian Conditions for Reuse in Irrigation

Abstract: High Rate Algal Pond (HRAP) was constructed and operated using a mixer device to investigate its capability in treating greywater for reuse in gardening. Physico-chemical and microbiological parameters were monitored. With a hydraulic retention time of 7.5 days and a solid retention time of 20 days, the average removal efficiencies (ARE) were 69% and 62% for BOD5 and COD respectively. The ARE for 3 NO − , 4 NH + and 4 PO 3− were 23%, 52% and 43% respectively. The removal of suspended solids (SS) was unsatisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…was typically not used for drinking or fishing and was only occasionally used for irrigation (Datta et al, 2021;Maiga et al, 2015). In the water, sediment, and adjoining soil samples, we quantified the DNA markers of the fecal indicator (Escherichia coli) to investigate the persistence of fecal bacteria; 16S rRNA gene copies to track the trends in the total bacterial count; and the anthropogenic antibiotic resistance gene markers-intI1, sul1, to investigate the overall trends in antibiotic resistance potential in WRPs.…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…was typically not used for drinking or fishing and was only occasionally used for irrigation (Datta et al, 2021;Maiga et al, 2015). In the water, sediment, and adjoining soil samples, we quantified the DNA markers of the fecal indicator (Escherichia coli) to investigate the persistence of fecal bacteria; 16S rRNA gene copies to track the trends in the total bacterial count; and the anthropogenic antibiotic resistance gene markers-intI1, sul1, to investigate the overall trends in antibiotic resistance potential in WRPs.…”
Section: Core Ideasmentioning
confidence: 99%
“…We sampled seven WRPs and contrasted them with two ponds (sites H and I) that did not directly receive domestic wastewater and were used for irrigation (P–I) and pisciculture (P–P), respectively. We observed that the water from the targeted WRPs was typically not used for drinking or fishing and was only occasionally used for irrigation (Datta et al., 2021; Maiga et al., 2015). In the water, sediment, and adjoining soil samples, we quantified the DNA markers of the fecal indicator ( Escherichia coli ) to investigate the persistence of fecal bacteria; 16S rRNA gene copies to track the trends in the total bacterial count; and the anthropogenic antibiotic resistance gene markers— int I1, sul 1, to investigate the overall trends in antibiotic resistance potential in WRPs.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients and carbondioxide (CO 2 ) from oxidation will be used by algae. HRAP waste treatment has some benefits that it is cost-effective and algae energy is converted to biofuel, biogas, and bio-ethane as biofuels [7], its reproduction is fast, non-pathogenic, the range of toxicity is extensive [8], useful for environmental sustainability [5], and environmentally friendly [9].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that have been conducted to examine the ability of microalgae in remediating polluted environments among others are HRAP in managing greywater on average can reduce biological oxygen demand (BOD 5 ) to 69%, chemical oxygen demand (COD) to 62%, NO 3 to 23%, NH 4 to 52%, PO 4 to 43% [7]. Bioremediation of Porphyra leucosticta red algae can reduce metals Cd(II) and Pb(I) with maximum capacities of 31.45 mg/g and 36.63 mg/g, respectively [10], Scenedesmus sp.…”
Section: Introductionmentioning
confidence: 99%